Synthesis of Some New Ligands as Drug Carrier - Nikkhoo-Amiry, Mahmod; Alami, Somaye; Ghaffar Ebadi, Abdol (Asian Journal of Chemistry, 2011)
In this research work, the preparation of new biscrown ether and lariat ether compounds as cationic and molecular acceptor are reported. For this purpose first, sulfoxide (1) was prepared by reaction of p-cresol with SOCl2 in 65 % yield. Then bisphonl (2) was prepared by reduction of compound (1) with Zn powder and acetic acid. Treatment of bisphenol (2) with methyl chloroacetate in the presence of K2CO3 and KI by refluxed in dry acetone gave dimethyl ester (3) in 98 % yield. Compound (5) was prepared by reaction of succinic acid and thionyl dichloride. Macrocyclic diamide (4) in 70 % yield was prepared by diamidation of diester (3) with diethylentriamine and then purified with recrystallization from methanol. Lariat ether compounds (8), (9), (10) were prepared by reaction of macrocyl (4) and henycosanoyl chloride, octanoyl chloride and 4-chloro boutanoyle chloride in 42, 38, 30 % yield. The structure of all prepared compounds has been established by 1H NMR, 13C NMR and IR.